A pilot comparison of the hang clean and hang snatch to the clean pull and snatch pull - Sanders, C.; Sevene, T. G.; Adams, K. J.; DeBeliso, M. (Journal of Athletic Enhancement, 2017)
Development of lower body strength and power is a primary goal of athletic-based strength and conditioning programs. Weightlifting and weightlifting derivatives are key components of these programs.